Management Of Advertising Activity In The Field Of Journalism - Agalarovna Guseinova, Aigul (2017)
Advertising activity has become an important element of the socio-economic policy system in the modern information society. It is obvious that advertising of domestic goods, works and services contributes to the growth of the budget of our country, and not the income of foreigners. Since the proceeds from sales goes to the wages of compatriots.If the goods are not competitive in its market, such advertising on the prepared soil is harmful. For example, when the country specifically created the conditions for increasing the cost of domestic products. No high-quality domestic goods will be able to compete with foreign ones because of the extremely high cost  due to a specially created and unfair tax burden for domestic production. The harmfulness of advertising in such conditions is hidden in a special way for an inefficient taxation system, etc. Therefore, in this article, the authors emphasize the importance of researching the content of advertising activities and its role in social and economic policy.